The Influence of Rice Straw Compost on Soil Quality, Fe2+ and SO4 2- Solubility, and Rice Yield in Acid Sulphate Soil - KHAIRIL ANWAR; SUPIYANDI SABIHAM; B. SUMAWINATA; A. SAPEI; T. ALIHAMSYAH (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2006)
Oxidation of pyrite in acid sulphate soil reduced the quality of soil. The improvement of soil quality in paddy cultivation could be managed by the addition of organic matter together with regulating water to maintain its reductive condition. The objective of this research was to obtain information on the ability of rice straw compost in improving soil quality and rice production. The research was conducted in acid sulphate soil(Typic Sulfaquepts), with flooding during high tide (B type) at experimental field Belandean, Research Institute for Swamp LandAgriculture (Balittra), South Kalimantan, during dry season of 2003. Treatment for improving soil quality was in the form of the rate of application of rice straw compost. Research results indicated that the application of rice straw compost was capable to improve soil quality during vegetative phase substantiated by increasing soil pH and organic matter content, and decreasing exchangeable Al, and also increasing Fe2+ and SO42- solubility. All of the soil chemical properties determine rice production, and Alexchangeable has the highest correlation. Application of rice straw compost as much as 2.7 t ha-1 (dry weight equivalent) wascapable to increase the yield of rice by 48%. This research results indicated that the rice straw from harvest should be returned to the paddy soil.